2003
DOI: 10.1159/000072897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Pressure Support and Proportional Assist Ventilation on Breathing Pattern, Work of Breathing and Gas Exchange in Mechanically Ventilated Hypercapnic COPD Patients with Acute Respiratory Failure

Abstract: Background: Proportional assist ventilation (PAV) has been shown to maintain better patient-ventilator synchrony than pressure support ventilation (PSV); however, its clinical advantage regarding invasive ventilation of COPD patients has not been clarified. Objectives: To compare the effect of PAV and PSV on respiratory parameters of hypercapnic COPD patients with acute respiratory failure (ARF). Methods: Nine intubated hypercapnic COPD patients were placed on the PAV or PSV mode in random sequence. For each m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
18
1
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 14 publications
3
18
1
7
Order By: Relevance
“…Such optional modes of assisted ventilation other than CPAP are adaptive pressure support servoventilation [2], bilevel positive airway pressure [7], and proportional assist ventilation [8]. Further studies are mandatory on which of these modes would be most favorable in an overall treatment strategy for CHF patients with CSR/CSA.…”
Section: Discussionmentioning
confidence: 99%
“…Such optional modes of assisted ventilation other than CPAP are adaptive pressure support servoventilation [2], bilevel positive airway pressure [7], and proportional assist ventilation [8]. Further studies are mandatory on which of these modes would be most favorable in an overall treatment strategy for CHF patients with CSR/CSA.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,12,21,[27][28][29][30] Navalesi and coworkers specifically characterized the consequences of increasing levels of VAV on total work of breathing over a wide range of support. 3 The reduction in elastic work achieved with VAV was offset in part by an increase in resistive work so that the decrease in total work of breathing was less than expected.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Respiration, Passam et al [5] analyzed in a physiologic study the response of sedated patients with chronic obstructive pulmonary disease to increasing levels of PSV and PAV. The most interesting characteristic of this paper is that low and high limits of PAV and PSV support were investigated.…”
mentioning
confidence: 99%
“…As a matter of fact, increasing levels of PSV were associated with an increasing number of inspiratory efforts not able to trigger the ventilator (missing efforts, ME), whereas increasing levels of PAV were associated with the occurrence of runaway breaths [1]. Passam et al [5] concluded that this different response cannot support the advantage of one method over the other since, despite the associated phenomena of each method, there is no limitation in blood gas improvement. However, lessons from mechanically ventilated patients with acute respiratory distress syndrome should remind us that not always arterial blood gas improvement has to be regarded as the main goal of ventilatory assistance in order to provide the patients with the most effective treatment [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation